Environmental generalism, holobiont interactions, and Pocilloporid corals in the warming oceans of the eastern coast of Australia - Bergman, Jessica L.; Richards, Zoe T.; Sawyers, Paige; Ainsworth, Tracy D. (Frontiers in Ecology and Evolution, 2023)
Ocean warming has been driving mortality events across the world's coral reef ecosystems and is resulting in multifaceted ecosystem restructuring. With the rapid shifts occurring across ecosystems, questions arise of which species, in which locations, have the capacity to persevere under climate change. Environmental generalism refers to species with the biological traits that support environmental flexibility, enabling the organism to occupy a broad range of environmental conditions. Some Scleractinia have been categorized as environmental generalists and proposed as likely winners under changing climate conditions, as environmental generalists have been considered less susceptible to environmental disturbance than specialist species. Given the complexity of the holobiont structure of corals, which includes photoendosymbiosis and diverse microbial consortia, understanding the complexity of the coral holobiont-environment interaction for the generalist corals will be an important factor in accurately predicting the success of these species into the future. Here we conduct a literature search to compile topics and concepts of environmental generalism for Australia's warming coral reef ecosystems and the breadth of holobiont responses to ecosystem restructuring. We synthesize these findings in the context of the latitudinal expanse of Australia's coral reefs to highlight how it is necessary to understand the biological underpinnings of generalist corals.